The influence of sterling on Irish interest rates - Thom, Rodney (Economic & Social Studies, 1995)
The influence of the Sterling real exchange rate on the Irish-German interest rate differential is assessed over the period 1987 to 1992. The estimation allows for structural change by permitting time variation in the model's parameters. Estimates derived using the Kalman Filter estimator suggest that the downward trend in the interest rate differential was a consequence of stable currency markets, with the real exchange rate close to its equilibrium level, rather than a totally credible exchange rate policy.
Keywords: Sterling; Exchange rates; Interest rates; Ireland